2019
DOI: 10.1002/jcp.29153
|View full text |Cite
|
Sign up to set email alerts
|

Exosome DNA: Critical regulator of tumor immunity and a diagnostic biomarker

Abstract: Nanosized cellular vesicles "exosome" contains a variety of biological cargo including DNA fragments from cell-of-origin. Despite its biological stability and clinical utility in tumor diagnosis, exosome DNA (ExoDNA) is very little studied as compare with exosome RNA. Cytoplasmic accumulation of damaged DNA from nucleus and mitochondria often leads to its packaging in exosomes by yet unknown pathways.ExoDNA modulates tumor immunity via paracrine interactions and activation of cytosolic DNA sensor pathways, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 114 publications
1
69
0
Order By: Relevance
“…LncRNA growth arrest-specific 5 (GAS5) mediated by exosomes was also identified as a promising serum-based biomarker for early non-small-cell lung cancer (NSCLC) diagnosis (77). It is widely proven that some exosomal DNAs, RNAs, proteins, and other bioactive molecules are emerging as critical and ideal noninvasive biomarkers for various benign and malignant diseases (78)(79)(80)(81)(82).…”
Section: Exosome Uptake and Functionmentioning
confidence: 99%
“…LncRNA growth arrest-specific 5 (GAS5) mediated by exosomes was also identified as a promising serum-based biomarker for early non-small-cell lung cancer (NSCLC) diagnosis (77). It is widely proven that some exosomal DNAs, RNAs, proteins, and other bioactive molecules are emerging as critical and ideal noninvasive biomarkers for various benign and malignant diseases (78)(79)(80)(81)(82).…”
Section: Exosome Uptake and Functionmentioning
confidence: 99%
“…27 Compared to RNA, people still know little about exosomal DNA. 28 Sansone et al reported that DNA fragments originated from either nucleus or mitochondria could be packaged into exosomes by an unknown pathway. 29 As containing specific mutation of parental cells, exosomal DNA could emerge as a diagnostic marker for disease.…”
Section: General Concept Of Evsmentioning
confidence: 99%
“…29 As containing specific mutation of parental cells, exosomal DNA could emerge as a diagnostic marker for disease. 28 However, new evidence indicated there might be no DNA in exosomes. Jeppesen et al reassessed the composition of exosomes and reported that the double-stranded DNA (dsDNA) associated histones were present in the nonvesicular (NV) components rather than in small EVs.…”
Section: General Concept Of Evsmentioning
confidence: 99%
“…Exosomal DNA, through regulation of cytoplasmic DNA sensing STING pathway, acts as a regulator of tumor immunity. Exosomal DNA exchange between tumor cells and dendritic cells regulate anti-tumor immunity [71]. Characteristics of glioma, especially GBM's aggressive invasion, metastasis, and recurrence, are attributed to its powerful immunosuppression.…”
Section: Pd-l1mentioning
confidence: 99%